Aberrant beta-band brain connectivity predicts speech motor planning deficits in post-stroke aphasia. (October 2022) - Sarmukadam, Kimaya; Behroozmand, Roozbeh
Abstract: Impairments in speech production can have devastating effects on the overall quality of life in left-hemisphere stroke survivors with aphasia; however, there is a paucity of research focusing on neural deficits in speech motor planning networks that are activated prior to the onset of speech production in this clinical population. In the present study, we examined directional brain connectivity correlates of speech preparation and planning in low-β (13–20 Hz) and high-β (21–30 Hz) band neural oscillations in participants aphasia compared with controls prior to the onset of speech. Electroencephalographic (EEG) data were concurrently recorded from 33 participants with post-stroke aphasia and 22 neurologically intact controls while they engaged in speech production tasks. Using Granger causality, brain connectivity was calculated between electrode pairs that fell within fronto-frontal, fronto-central, and fronto-parietal networks implicated in sensorimotor integration and speech planning. Clinical assessment was further conducted in post-stroke participants to measure the severity of language impairment associated with aphasia. Increased intra-hemispheric connectivity was found within low- and high-β bands in the left parieto-central and parieto-frontal as well as the right fronto-frontal and fronto-central electrodes in post-stroke participants compared with controls prior to the onset of speech production. In addition, we found that decreased inter-hemispheric centro-central connectivity within high-β band was negatively correlated with aphasia severity whereas increased parieto-frontal connectivity within high-β band was positively correlated with aphasia severity. These findings suggest that participants with left-hemisphere stroke express aberrant brain connectivity within low- and high-β bands in both left and right hemispheres during the planning phase of speech production, and that these deficits are associated with specific aspects of their language impairment, as indicated by their clinical symptoms due to aphasia.